2014
DOI: 10.5888/pcd11.140342
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Daily Consumption of Sugar-Sweetened Beverages Among Adult Patients at Four Federally Qualified Health Centers, Bronx, New York, 2013

Abstract: IntroductionConsumption of sugar-sweetened beverages (SSBs) is associated with cardiovascular disease risk factors. This study examined the relationships between SSB consumption and demographic, health behavior, health service, and health condition characteristics of adult patients of a network of federally qualified health centers (FQHCs) in a low-income, urban setting. MethodsValidated, standardized self-reported health behavior questions were incorporated into the electronic health record (EHR) and asked of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Overall, compared to non-smokers, both non-daily and daily smokers were 1.24 to 1.34 times more likely to consume regular soda than no soda. These findings are consistent with previous findings demonstrating that adults consuming >1 SSB daily were more likely to be current smokers versus never smoking ( Kristal et al, 2015 ). Clustering of smoking and other high-risk behaviors has been recognized among both adolescents and young adults, and may reflect an overall higher propensity for risk taking ( Colby et al, 2017 ; Hair et al, 2009 ; Jessor, 1991 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, compared to non-smokers, both non-daily and daily smokers were 1.24 to 1.34 times more likely to consume regular soda than no soda. These findings are consistent with previous findings demonstrating that adults consuming >1 SSB daily were more likely to be current smokers versus never smoking ( Kristal et al, 2015 ). Clustering of smoking and other high-risk behaviors has been recognized among both adolescents and young adults, and may reflect an overall higher propensity for risk taking ( Colby et al, 2017 ; Hair et al, 2009 ; Jessor, 1991 ).…”
Section: Discussionsupporting
confidence: 93%
“…Young adults are also among the greatest consumers of sugar-sweetened beverages (SSB) ( Dietary Guidelines Advisory Committee, 2015 ), which account for almost half of all added sugars consumed by the U.S. population ( U.S. Department of Health and Human Services and U.S. Department of Agriculture, 2016 ). High SSB intake in young adults is strongly associated with race, education, and economic factors ( Han and Powell, 2013 ; Park et al, 2016a , Park et al, 2016b ), has been shown to vary by geographic location ( Park et al, 2016a , Park et al, 2016b ), and to be associated with other high-risk behaviors such as low physical activity ( Kristal et al, 2015 ; Park et al, 2016a , Park et al, 2016b ), smoking ( Kristal et al, 2015 ; Park et al, 2016a , Park et al, 2016b ), and alcohol intake ( Park et al, 2016a , Park et al, 2016b ). Soda is the most heavily consumed SSB by young adults ( Han and Powell, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Children's Health Insurance Program (CHIP) or Children's Medicaid). While using insurance type as a proxy for SES is far from ideal, insurance coverage is widely used as a marker for individual-level SES with reasonable validity (Goyal et al 2011;Casey et al 2013;Kristal et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…While it is not ideal to use insurance type as a proxy for SES, publicly provided health care coverage such as Medicaid is only available to children who meet stringent income criteria, with the exception of some that suffer from limited medical conditions (Rosenbaum 2002). In addition, insurance coverage is widely used as a marker for individual-level SES with reasonable validity and reliability (Goyal et al 2011;Casey et al 2013;Kristal et al 2015). Future researchers should apply a more comprehensive set of covariates to test the reliability of our findings, and include individual-and familylevel conditions known to track with obesity (e.g., parenting behaviors, peer group influences).…”
Section: Limitationsmentioning
confidence: 99%
“…However, not all SSBs contain caffeine, and many of the standard measures used to capture SSB consumption do not differentiate beverages on caffeine content ( Riordan et al, 2017 ). Regardless of caffeine content, SSBs have demonstrated the same positive association between consumption and smoking as coffee in adults ( Kearns et al, 2018 , Kristal et al, 2015 ). As youth demonstrate different caffeinated beverage consumption patterns as compared to adults, identifying which caffeinated beverage source has the strongest association with smoking behaviour may help to inform health policy for this population.…”
Section: Introductionmentioning
confidence: 99%